EFFECTS OF FEEDING THYMOL AND ISOEUGENOL ON PLASMA TRIGLYCERIDES AND CHOLESTEROL LEVELS IN JAPANESE QUAIL - A. Luna; M. C. Lábaque; M. E. Fernandez; J. A. Zygadlo; R. H. Marin (Journal of Animal and Plant Sciences, 2018)
Dietary supplementation can be considered one of the main strategies to include new additives with beneficial effects into animal products. Thymol supplementation has shown to improve oxidative stability of eggs and meat during storage and also to increase the relative composition of polyunsaturated fatty acids. Feed supplementation with isoeugenol has shown to increase hatching success. The present study evaluates supplementation with thymol and isoeugenol on plasma lipid profile in Japanese quail. At 4 weeks of age, 48 males and 96 females were housed in groups of 1 male and 2 females and assigned during 10 weeks to 1 of 4 diet treatments: vehicle or 400 mgkg-1 of butylated-hydroxytoluene (controls), and 400 mg kg-1 of thymol or isoeugenol. Body weight, growth rate, and egg production were determined. At 14 weeks of age, plasma lipids (total cholesterol, HDL-cholesterol, LDL-cholesterol and triglycerides) were also determined. Results demonstrated that supplementation with thymol and isoeugenol increased female triglycerides compared to males and to control females. No triglyceride changes were induced by butylated-hydroxytoluene. Body weight, growth rate and egg production were not affected by dietary treatments. The increased plasma triglycerides observed in female birds may have biological relevance to better sustain the metabolic needs during laying period. These results contribute to show the potential usefulness of these essential oil main components as natural feed supplement alternatives for poultry.
Keywords: Essential oil component; diet; poultry; phytogenic feed additive; plasma lipid